(untitled) (Revista Científica Integrada, 2023)
Objective: To relate the activities carried out during the extension project “Health promotion and prevention of COVID-19 in elderly people living alone”. Methods: Experience report on the activities carried out during the execution of the extension project “Health promotion and prevention of COVID-19 in elderly people living alone”, developed within the scope of a public university, by professors and students of the Nursing course, from July to December 2020, with 38 elderly people who lived alone and had a cell phone, registered, and assisted in the Basic Health Units of a municipality in Piauí. Results: Telephone calls were made to the elderly, with an average duration of 29 minutes, in which general guidelines were given 116 (45%), cognitive games were played 62 (24%), recreational activities 41 (16%) and other activities 36 (14%). Conclusions: The extension actions developed during the extension project aimed to contribute to improving the well-being of the elderly who live alone during the pandemic period, through the development of health education activities, promotion and prevention of COVID-19 and the vulnerabilities awakened by social distancing.